Analysis of Berths Acceleration Strengthening Project Regarding Time Control (Case Study of Container Terminal in Jakarta) - Irawan Jodarwanto; Ervina Ahyudanari (Journal Research of Social Science, Economics, and Management, 2025)
Port infrastructure projects face unique challenges in maintaining operational continuity while executing complex structural modifications, especially in terminals operating 24 hours with strict time and technical constraints. The berthing reinforcement project at XYZ Container Terminal aimed to accommodate container ships up to 100,000 DWT and support the Super Post Panamax Quay Container Crane. Scheduled for 297 days, the project is located at an operational berth. During implementation, disruptions caused a -6.853% deviation in achievement weight in week 8 and risked delays. This research analyzes acceleration methods using the Critical Path Method, comparing Fast Track and Crashing techniques. Quantitative analysis with Microsoft Project includes adding drilling machines, adding labor (Crashing), and adjusting the Partial Hand Over (PHO) stages (Fast Track). Fast Track with PHO 2 stages accelerated completion to 296 days (0.34%) with a 0.10% cost increase; PHO 3 and 4 stages shortened it to 295 days (0.67%) with a 0.21% cost increase. Crashing shortened completion to 285 days (4.04%) but increased costs by 0.13%. The 4-stage PHO configuration shows superior operational efficiency by segmenting work areas to minimize disruptions, achieving faster completion than planned, and meeting Box Per Ship Per Hour (BSH) targets with minimal extra costs. This research offers a practical framework for selecting acceleration methods in port infrastructure projects requiring phased handovers and workspace optimization.